Atmospheric neutrino oscillation analysis with improved event reconstruction in Super-Kamiokande IV. (14th May 2019) - Jiang, M; Abe, K; Bronner, C; Hayato, Y; Ikeda, M; Iyogi, K; Kameda, J; Kato, Y; Kishimoto, Y; Marti, L l; Miura, M; Moriyama, S; et al.
Abstract: A new event reconstruction algorithm based on a maximum likelihood method has been developed for Super-Kamiokande. Its improved kinematic and particle identification capabilities enable the analysis of atmospheric neutrino data in a detector volume 32% larger than previous analyses and increase the sensitivity to the neutrino mass hierarchy. Analysis of a 253.9 kton· year exposure of the Super-Kamiokande IV atmospheric neutrino data has yielded a weak preference for the normal hierarchy, disfavoring the inverted hierarchy at 74% assuming oscillations at the best fit of the analysis.